Landasan Psikologis Pendidikan Kristen dan Relevansinya dalam Pendidikan Kristen Masa Kini - Paulus Kunto Baskoro (Jurnal Pendidikan Agama Kristen (JUPAK), 2020)
Building a family, church, educational institution or business world cannot be separated from the concept of an education. Education is an important reference in seeing, directing and bringing about a very significant and maximum change. By using descriptive descriptive method, through the literature study approach, research can describe the journey of education in a person, family, educational institution, church or business world, which cannot be separated from the psychological element which is the basis for further understanding. This is because there are many people who have not taken Christian education seriously in the family, work environment, even in churches with a clear curriculum. In the context of this discussion, education is focused on Christian education. It is very necessary to build a strong psychological foundation in Christian education, so that it can be used as a reference in building an ideal and maximum Christian education. The principles in this presentation will formulate some of the psychological foundations which are the foundation of Christian education. Because Christian education is very important in building a wholeness of view that is in accordance with the truth of God's Word and the character of Christ.